Estimation of the reduction of produced water discharge through the application of relative permeability modifier - Martínez López, Raúl Andrés; Santos Santos, Nicolás; Carrillo Moreno, Luis Felipe; Torres Doria, Luis Alejandro (CT&F - Ciencia, Tecnología y Futuro, 2024)
The management of produced water is a significant environmental challenge, particularly considering the goal to achieve 'Water Neutrality' by 2045, which requires the entire elimination of discharges into water bodies. In Colombia, discharged water currently accounts for over 30% of total water production, approximately 80 million m3, which adversely affect various ecosystems. Moreover, the economic implications are substantial, as each barrel of produced water represents a significant quantity of unextracted oil, impacting the fields’ profitability. To address this issue, various stimulation methods have been used to mitigatewater production. This study is intended to assess the efficacy of these techniques in reducing water production and improving environmental management. The Universidad Industrial de Santander, through its specialized services to the hydrocarbon industry, has conducted numerous assessments of relative permeability modifier (RPM) treatments across diverse scenarios and conditions. These evaluations have revealed high reduction in water permeabilities of up to 90%, effectively curbing water contributions from producer wells. This approach not only yields tangible benefits for companies by averting treatment costs, but also translates into environmental benefits through reduced water discharge. In this study, we leverage this expertise to assess the potential impact of RPM treatments on water production. By analyzing changes in relative permeability curves via reservoir simulation, we aim to estimate the prospective decrease in water production and, consequently, the reduction in oil industry discharges in Colombia prior to a widespread implementation of this technique.